2012
DOI: 10.1371/journal.pone.0038663
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study in a Lebanese Cohort Confirms PHACTR1 as a Major Determinant of Coronary Artery Stenosis

Abstract: The manifestation of coronary artery disease (CAD) follows a well-choreographed series of events that includes damage of arterial endothelial cells and deposition of lipids in the sub-endothelial layers. Genome-wide association studies (GWAS) of multiple populations with distinctive genetic and lifestyle backgrounds are a crucial step in understanding global CAD pathophysiology. In this study, we report a GWAS on the genetic basis of arterial stenosis as measured by cardiac catheterization in a Lebanese popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
(51 reference statements)
3
44
0
Order By: Relevance
“…This result is similar to that reported by Beaudoin et al [16], who performed electrophoretic mobility shift assays (EMSA) with HUVEC nuclear extracts and demonstrated the interaction between the rs9349379 polymorphism and the MEF2 factor. A GWAS performed in a Lebanese study recently confirmed the association of the PHACTR1 (rs9349379) gene polymorphism with coronary artery stenosis [5]. We agree with this report, since our data confirmed that the rs9349379 polymorphism is associated with premature CAD in a Mexican population.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to that reported by Beaudoin et al [16], who performed electrophoretic mobility shift assays (EMSA) with HUVEC nuclear extracts and demonstrated the interaction between the rs9349379 polymorphism and the MEF2 factor. A GWAS performed in a Lebanese study recently confirmed the association of the PHACTR1 (rs9349379) gene polymorphism with coronary artery stenosis [5]. We agree with this report, since our data confirmed that the rs9349379 polymorphism is associated with premature CAD in a Mexican population.…”
Section: Discussionsupporting
confidence: 91%
“…Detailed clinical and demographic information have been previously described [2] (Additional file 1). 406 out of the 991 participants had >50% stenosis in at least one vessel and were designated as severe CAD patients, 207 had stenosis ≤50% in at least one vessel and were designated as moderate CAD patients, and 378 had 0% stenosis and were classified as controls.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was replicated for association with various forms of coronary artery disease [2, 3] and ischemic stroke [4]. It has also shown significant association with coronary artery calcification, which is a major risk factor for coronary artery disease [5].…”
Section: Introductionmentioning
confidence: 81%
“…Several further studies have confirmed its association with coronary artery disease [3, 810] and coronary artery calcification [7, 11]. Due to strong linkage disequilibrium with rs12526453 SNP on the haplotype level, the associations of rs9349379 may be extended to rs12526453.…”
Section: Introductionmentioning
confidence: 98%